The Effect of Accounting Based on Financial Accounting Standards For Micro, Small and Medium Entities (SAK-EMKM) on The Quality of Financial Reports (Case Study on Msmes In Simpang Empat District, Asahan Regency) - Indah Malau; Maf Taufiq; Handriyani Dwilita (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This research was conducted on MSMEs in Simpang Empat District, with the aim of analyzing the impact of SAK-EMKM-based accounting on the financial report quality of MSMEs in Simpang Empat District. The study employs a quantitative approach with an associative type that refers to causal relationships. The population in this research consists of 83 MSMEs in Simpang Empat District, with the sample selected using random sampling. The data sources in this study include primary and secondary data, and data collection techniques involve literature studies, surveys, and observations. The data analysis techniques used in this study are data quality tests, classical assumption tests, simple linear regression, and hypothesis testing. The results of the study indicate that SAK-EMKM-based accounting has a positive and significant effect on the financial report quality of MSMEs in Simpang Empat District. SAK-EMKM-based accounting shows a strong correlation with the financial report quality of MSMEs in Asahan District. The percentage of financial report quality that can be explained by SAK-EMKM-based accounting is 70.2%, while the remaining 29.8% can be explained by other variables outside the scope of this research.